A High Directivity Microstrip Coupler Based on Reflective Resistors - Guo, L.; Wei, Y. J.; Shi, Y. P.; Zou, X. J.; Wang, G. M. (Společnost pro radioelektronické inženýrství, 2024)
In this paper, a novel high-directivity microstrip coupler based on reflective resistors is presented. The proposed coupler consists of three pairs of coupled-line sections and one pair of resistors. Generally, the coupling degree can be controlled by the coupled-lines, while the resistors are employed to adjust the amplitude of the reflected signal to cancel out the leakage signal. The mechanism of high directivity is derived and the S-parameters are presented. To verify the design concept, a 20 dB microstrip coupler operating at 2 GHz is processed and measured. The measured results indicate that the return loss of input and output ports is more than 28.5 dB with a typical insert loss of 0.3 dB, while that of coupled and isolated ports is more than 15 dB. And the directivity is more than 20 dB with a maximum 53.1 dB at 2.01 GHz in a fractional bandwidth of 22.5%.
Keywords: High directivity; microstrip coupler; S-parameters